2014
DOI: 10.1016/j.bjid.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis associated with boceprevir: a case report

Abstract: Approximately 170 million people are infected with hepatitis C, and the sustained virological response rate to treatment with pegylated interferon and ribavirin is 30-50%. In an attempt to improve the chances of cure, boceprevir is being added to therapy, but it is associated with an increased incidence of adverse events. We herein report a case of acute pancreatitis developed during treatment with pegylated interferon, ribavirin and boceprevir. Boceprevir was the most likely cause of drug-associated pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This analysis also found use of interferon to be associated with a higher prevalence of acute pancreatitis in patients with HCV infection (2.7%). Pancreatitis has also been observed in patients receiving telaprevir and boceprevir in combination with PR, and as an adverse event during treatment with sofosbuvir and ribavirin . In the telaprevir core clinical trial programme, pancreatitis was reported in 7/2669 (0.3%) patients treated with telaprevir in combination with PR; however, there were no cases of pancreatitis in the 764 patients treated with PR alone .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis also found use of interferon to be associated with a higher prevalence of acute pancreatitis in patients with HCV infection (2.7%). Pancreatitis has also been observed in patients receiving telaprevir and boceprevir in combination with PR, and as an adverse event during treatment with sofosbuvir and ribavirin . In the telaprevir core clinical trial programme, pancreatitis was reported in 7/2669 (0.3%) patients treated with telaprevir in combination with PR; however, there were no cases of pancreatitis in the 764 patients treated with PR alone .…”
Section: Discussionmentioning
confidence: 99%
“…According to individual case reports, other drugs with a less obvious association with AP are atazanavir, darunavir, and boceprevir [20,120]. The first two were not included in the Wolfe and Simons-Linares classification, but pancreatitis is listed in the product information as a risk factor and/or adverse drug reaction (ADR) [10].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Recently, the high safety profiles associating DAAs had denied any linkage with DIP occurrence. However, boceprevir and telaprevir were mentioned in such a fatal condition in two separate reports [37,38]. Conversely, later generations of DAAs had been mentioned to cause DIP only in cases with ribavirin including regimens.…”
Section: Anticancer Therapiesmentioning
confidence: 99%